Chimeric Activators and Repressors Define HY5 Activity and Reveal a Light-Regulated Feedback Mechanism. Issue 4 (21st February 2020) - Burko, Yogev; Seluzicki, Adam; Zander, Mark; Pedmale, Ullas V.; Ecker, Joseph R.; Chory, Joanne
Abstract : HY5 promotes activation rather than repression of its direct targets, including SPA1, revealing a light-regulated feedback mechanism. Abstract: The first exposure to light marks a crucial transition in plant development. This transition relies on the transcription factor HY5 controlling a complex downstream growth program. Despite its importance, its function in transcription remains unclear. Previous studies have generated lists of thousands of potential target genes and competing models of HY5 transcription regulation. In this work, we carry out detailed phenotypic and molecular analysis of constitutive activator and repressor HY5 fusion proteins. Using this strategy, we were able to filter out large numbers of genes that are unlikely to be direct targets, allowing us to eliminate several proposed models of HY5's mechanism of action. We demonstrate that the primary activity of HY5 is promoting transcription and that this function relies on other, likely light-regulated, factors. In addition, this approach reveals a molecular feedback loop via the COP1/SPA E3 ubiquitin ligase complex, suggesting a mechanism that maintains low HY5 in the dark, primed for rapid accumulation to reprogram growth upon light exposure. Our strategy is broadly adaptable to the study of transcription factor activity. Lastly, we show that modulating this feedback loop can generate significant phenotypic diversity in both Arabidopsis ( Arabidopsis thaliana ) and tomato ( Solanum lycopersicum ).